B.3 The incidence of perinatal stroke is 1:1200 births in Southern Alberta: Population-based incidence of disease-specific perinatal stroke. (November 2021) - Dunbar, M; Hodge, J; Floer, A; Kirton, A
Abstract : Background: Perinatal stroke encompasses six cerebrovascular syndromes which occur between the 20 th week of gestation and the 28 th post-natal day. Subtypes are neonatal arterial ischemic stroke (NAIS), neonatal cerebral sinovenous thrombosis (CSVT), neonatal hemorrhagic stroke (NHS), arterial presumed perinatal ischemic stroke (APPIS), periventricular venous infarction (PVI), and presumed perinatal hemorrhagic stroke (PPHS). Inconsistent terminology and lack of population-based case series has limited accurate measurement of disease-specific perinatal stroke incidence. Our objective was to define the incidence of the subtypes of perinatal stroke using a population-based cohort. Methods: The Alberta Perinatal Stroke Project is a research cohort established in 2008 in Southern Alberta. Case acquisition included retrospective hospital and ICD code searches (1990-2008) and prospective enrollment from all NICU and neurology/stroke clinics (2008-2017). Results: The overall incidence of perinatal stroke in Southern Alberta was 9.0 cases per 10, 000 births, or 1:1200 births. Per 10, 000 births, the incidence of each subtype was: NAIS = 3.2 (~1:3000), APPIS =1.2 (~1:8500), PVI = 1.5 (~1:6500), CSVT = 1.0 (~1:9900), NHS = 1.4 (~1/7300), PPHS = 0.1 (1/82, 000). Conclusions: The overall incidence of perinatal stroke in Southern Alberta is 1:1200 live births. Population-based sampling of disease-specific states may explain why this rate is much higher than previous estimates